Про задачу розробки електронного комплексу зі створення наборів тривимірних моделей спеціального призначення - Ліхініна, Р. В. (ХНУРЕ, 2024)
Currently, there are a large number of multi-user computer electronic complexes for solving ordinary or everyday tasks. But if we are talking about more specialized, specific or niche topics, the number of such tools is either significantly less, or they do not exist at all. That is why there is a need to design and develop appropriate complexes according to the needs of users. The next work involves the creation of sets of three-dimensional objects that will meet the occupational health and safety standards. Below are the topics and requirements for the selected development topic, as well as the necessary functions and tasks that must be performed to use it.
Keywords: розробка електронного комплексу